Whole Systems Trade Analysis. Issue 1 (October 2015) - Edwards, Shatiel; Cilli, Matthew; Peterson, Troy; Zabat, Michael; Lawton, Craig; Shelton, Liliana
Abstract: Ground vehicles are complex systems with many interrelated subsystems – finding the sweet‐spot among competing objectives such as performance, unit cost, operations and sustainment (O&S) costs, development risk, and growth potential is a non‐trivial task. Whole Systems Trade Analysis (WSTA) is a systems analysis and decision support methodology and tool that integrates otherwise separate subsystem models into a holistic system view mapping critical design choices to consequences relevant to stakeholders. WSTA projects are highly integrated and collaborative efforts which generate holistic systems and Multiple Objective Decision Analysis (MODA) models. The related tool captures and synthesizes subsystem and system level analyses into trade‐space visualizations designed to facilitate rapid and complete understanding of the trade‐space to stakeholders and provide drill down capability to supporting rationale. The approach has opened up trade space exploration significantly evaluating up to 10 20+ potential system configurations to then return a handful of configurations which best meet design and programmatic criteria.